Assessment of diaphragm motion using ultrasonography in a patient with facio-scapulo-humeral dystrophy: A case report. Issue 4 (January 2019) - Fayssoil, Abdallah; Stojkovic, Tanya; Ogna, Adam; Laforet, Pascal; Prigent, Helene; Lofaso, Frederic; Orlikowski, David; Bassez, Guillaume; Eymard, Bruno; Behin, Anthony
Abstract: Rationale: Diaphragm is the main inspiratory respiratory muscle and little is known about diaphragm ultrasound in facio-scapula-humeral muscular dystrophy, a neuromuscular disease characterized by an asymmetric skeletal muscle involvement. Patient concerns: Diaphragm function evaluation Diagnosis: Diaphragm muscle weakness attested by the drop of vital capacity (VC) value from sitting position (74%) to supine position (46%). Interventions: A diaphragm ultrasound was performed in supine position, from the anterior subcostal window Outcomes: We found an opposite side to side hemi diaphragm displacement, either during sniff maneuver or during deep inspiration maneuver, showing a cranial abnormal reduced motion of the right hemi diaphragm whereas the left hemi diaphragm moved caudally. Lessons: Diaphragm weakness may be present with an asymmetric pattern and an opposite motion during inspiration or sniff manoeuver in facio-scapula-humeral muscular dystrophy. A future study with a systematic evaluation of a greater number of FSHD1 patients will be necessary to characterize this population.